Harnessing the Multilingual Factors of Nigeria for Development: The Challenges and Strategies - Ògúnwálé, Joshua Abíódún (Mediterranean Journal of Social Sciences, 2012)
The arbitrary and haphazard territorial boundaries imposed by the colonial powers in the last twocenturies or so did not take cognizance of the people’s diversities before differentiating Nigeria and othersub-Saharan African states. As a result, the geo-political enclave now known as a country encompassespeople with varying linguo-cultural identities. This has continued to have far reaching effects on the socioeconomicpotentials of the nation. It is further argued that the post-independence Nigeria’s slow pace onthe road of progress is largely due to the non-participation of the Nigerian mono-lingual majority in thesocio-economic and political affairs of the nation. This is either as a result of the non-availability, nonutilizationor defective language policy, or its absence, that is geared towards the use of mother-tongues.This paper, however contends that positive results can still be gleaned from the resourceful utilization andpositive involvements of the Nigerian factors despite her multilingualism. An empirical survey on the areaof activities where English domination is mostly manifested was conducted among some secondary schoolslocated in the south western part of Nigeria. It was found that European influence had continued to haveseries of devastating effects on the self actualization ethos of the nation because wealth of indigenousknowledge was being locked away in the local languages and was gradually being lost as the custodians ofthese knowledge passed on. It is conclusively posited, therefore, that sustainable developments of theNigerian individual and society only reside in turning a new leaf to the involvement of mother-tongues inthe production and consumption of the world knowledge.